Preface - Agrati, Laura Sara; Burgos, Daniel; Ducange, Pietro; Limone, P.; Perla, L.; Picerno, P.; Raviolo, P.; Stracke, C.M. (Communications in computer and information science, 2021)
Preface
Keywords: preface; Scopus(2)